The impact of intrinsic muscle properties on simulated reaching performance. Issue 7 (19th May 2023) - Murtola, Tiina; Richards, Christopher
Abstract: Musculoskeletal modelling is used widely for studying limb motion and its control, but simulation outcomes may depend heavily on the underlying muscle model used. The aim of this study was to investigate how intrinsic muscle properties affect reaching movements in a simple upper limb model. The simulations suggest that more realistic, higher-order activation dynamics requires longer prediction from a forward model and gives rise to a higher level of unplanned co-contraction than simple activation models. Consistent with prior work, muscle force-length-velocity properties stabilised and smoothed limb movements and furthermore helped promote accurate reaching performance with the high-order activation model.